Improving Atrial Fibrillation Detection in Patients with Implantable Cardiac Devices by Means of a Remote Monitoring and Management Application. Issue 12 (12th August 2014) - ZOPPO, FRANCO; FACCHIN, DOMENICO; MOLON, GIULIO; ZANOTTO, GABRIELE; CATANZARITI, DOMENICO; ROSSILLO, ANTONIO; BACCILLIERI, MARIA STELLA; MENARD, CECILE; COMISSO, JENNIFER; GENTILI, ALESSANDRA; GRAMMATICO, ANDREA; BERTAGLIA, EMANUELE; et al.
<x xml:space="preserve">Abstract</x> Background Atrial fibrillation (AF) is common in patients with cardiac implantable electronic devices (CIED) and has been associated with an increased stroke risk. The aim of our project was to assess the clinical value of a web‐based application, Discovery Link AFinder, in improving AF detection in CIED patients. Methods and Results Seven Italian hospitals performed an observational study consisting of four phases. During phase 1, expert nurses and cardiologists prospectively followed‐up CIED patients via in‐hospital examinations and remote monitoring, and classified clinically relevant events, particularly AF occurrence. During phase 2, Discovery Link AFinder was exploited to identify patients who had suffered AF in the previous 12 months through the systematic scanning of device data remote transmissions. Phases 3 and 4 were repetitions of phases 1 and 2, respectively, and were implemented 6 months after the previous phases. A total of 472 consecutive patients were included in phase 1; AF occurred in 170 patients, 61 of whom were identified as new AF patients. Evidence of AF during this phase prompted prescription of oral anticoagulation (OAC) therapy in 30 patients. In phase 2, AFinder uncovered new AF, unidentified in phase 1, in 54 patients and prompted implementation of OAC therapy in 11 patients. During phase 3, 30 new AF patients were identified by means of remote monitoring, while during phase 4, a further three AF patients were identified by AFinder only. Conclusions The AFinder web‐based software, applied on top of standard in‐hospital and remote monitoring, improved AF detection and enabled OAC treatment to be undertaken.